Związki nauki administracji z innymi dyscyplinami wiedzy - Wrzosek, Stanisław (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
Due to very complex structure and functioning public administration is the subject of interest of many academic disciplines. Research on public administration is primarily an issue of administrative science. Administrative science uses attainments of other legal science as well as social and economic sciences. This results in large changes in the research on public administration. A general theory of administration may become a base for research on administration.
Keywords: system; scientific method; general theory of systems; legal science; the general theory of administration; political science; sociology; academic discipline; public administration; management science; the science of administrative law; the science of social policy; administrative science